Variação temporal da resistividade elétrica em contaminação por gasolina - Braga, Antonio Celso de Oliveira [UNESP]; Moreira, César Augusto; Cardinali, Maira Tozzi [UNESP] (My University, 2008)
The definition of models and base parameters for application of investigation tools in environment with high complexity are a basic premise to any sciences. The geophysics is a science with solid theoretical base and applications in diversified areas of the sciences geological, astronomical, meteorological, among many others. Its application in environmental studies is relatively recent and needs further research. To understand the behavior of resident contaminants in a dynamic and complex environment as the geological, it requests studies in scale laboratorial, under control of factors seasonality variable. This work simulates a leak of gasoline in soil, under conditions and in laboratory scale, with the objective of monitoring the temporary behavior of the hydrocarbon under the optics of variation of the parameter physical electric resistivity. The results indicate increase of the resistivity in recent periods the contamination, followed for stability in the values and finally fall and return tendency to the natural conditions.

A definição de modelos e parâmetros de base para aplicação de ferramentas de investigação de ambientes com elevada complexidade é uma premissa básica a quaisquer ciências. A Geofísica é uma ciência com sólida base teórica e aplicações em áreas diversificadas das ciências geológicas, astronômicas, meteorológicas, dentre muitas outras. Sua aplicação em estudos ambientais é algo relativamente recente e que necessita de pesquisas aprofundadas. Compreender o comportamento de contaminantes residentes num ambiente dinâmico e complexo como o geológico, requer estudos em escala laboratorial, sob controle de fatores sazonalmente variáveis. Este trabalho simula um vazamento de gasolina em solo, sob condições e em escala de laboratório, com o objetivo de monitorar o comportamento temporal do hidrocarboneto sob a ótica de variação do parâmetro físico resistividade elétrica. Os resultados indicam aumento da resistividade em períodos recentes a contaminação, seguido por estabilidade nos valores e finalmente, queda e tendência de retorno às condições naturais. Palavras-chave: hidrocarboneto, gasolina, resistividade, atenuação natural, monitoramento.
Temporal variation of electrical resistivity in contamination for gasoline
Keywords: Gasoline; Hydrocarbon; Monitoring; Natural attenuation; Resistivity; ecological approach; electrical resistivity; geological theory; geophysics; hydrocarbon; natural attenuation; pollution monitoring; seasonal variation; soil pollution; temporal period; temporal variation; volatile organic compound